2018
DOI: 10.1016/j.vprsr.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Toxoplasma gondii from pigs in Yucatan, Mexico

Abstract: Ti t l e G e n o ty pi n g of Toxo pl a s m a g o n dii fro m pi g s in Yuc a t a n, M exic o

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The first of them (A/G, 159 position) is a type II strain SNP, while the second (A/G, 110 position) has been reported in sequences isolated from China (GenBank® KU599378, KU599384, KU599385, and KU599386); however, both sequences are new. The finding of sequences that carry unique SNPs in Mexico has also been reported in pigs from Yucatan: Cubas-Atienzar et al [ 15 ] found 18 different Alt. SAG2 sequences in addition to the I and III classic alleles in blood and muscle samples of 40 swine.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The first of them (A/G, 159 position) is a type II strain SNP, while the second (A/G, 110 position) has been reported in sequences isolated from China (GenBank® KU599378, KU599384, KU599385, and KU599386); however, both sequences are new. The finding of sequences that carry unique SNPs in Mexico has also been reported in pigs from Yucatan: Cubas-Atienzar et al [ 15 ] found 18 different Alt. SAG2 sequences in addition to the I and III classic alleles in blood and muscle samples of 40 swine.…”
Section: Discussionmentioning
confidence: 64%
“…Mixed infections due to T. gondii are demonstrated by PCR-RFLP when more than one restriction pattern is visualized and by sequencing when two peaks overlap due to different nucleotides at the same position [ 11 , 14 , 15 ]. However, one disadvantage of PCR-RFLP is that a maximum of three coinfections can be suspected when the restriction patterns of the three classic alleles are visualized for a given locus, just as we reported for the SAG3 marker in clinical samples from feral cats in Quintana Roo [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In México, the presence of more than one strain in a given host has become rather common, because it has been described in animals from neo-tropical regions of México, i.e. in feral cats from Quintana Roo, stray dogs from Chiapas and pigs from Yucatán ( Cubas-Atienzar et al, 2018 ; Valenzuela-Moreno et al, 2019 , 2020 ). However, this phenomenon is not exclusive to those regions, since in human congenital cases from the Valley of Mexico, and now in mouflons from Puebla (both neo-artic regions) we have found mixed infections as well ( Rico-Torres et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The attempt to pinpoint the organs and meat cuts most likely to contain significant numbers of tissue cysts and which present the highest risk for the consumer is important. In fact, T. gondii cysts were detected in most examined tissues of pigs intended for human consumption, including the heart, diaphragm, brain, liver, tongue, masseter muscle and raw ham (Paraboni et al, 2020;Miura et al, 2019;Paştiu et al, 2019;Cubas-Atienzar et al, 2018;Vergara et al, 2018;Kuruca et al, 2017;Franco-Hernandez et al, 2016;Hernández-Cortazar et al, 2016;Herrero et al, 2016;Cademartori et al, 2014;Dubey et al, 2012), and the parasite was even isolated from the blood of market-weight pigs (Klun et al, 2011).…”
Section: Raw Pork -Risky Cutsmentioning
confidence: 99%